Qualidade da carne de cordeiros alimentados na fase de terminação com caroço de algodão - Pellegrini, Luiz Gustavo de (2017)
The objective of this study was to evaluate the effect of cotton seed in the diet of lambs (0, 100, 200, 300 and 400 g kg-¹) on sensory analysis, fatty acid and amino acid profile, volatile organic compounds, Instrumental evaluation of flesh color. The aim of this study was to evaluate the effect of whole cottonseed (0, 100, 200, 300 and 400 g kg-¹) in the diet of lambs in terms of sensory analysis, the profiles of fatty acids and amino acids, volatile organic compounds, physico-chemical characteristics and instrumental evaluation of color in the meat. A total of 45 male, uncastrated male Ile de France lambs with mean initial body weight of 16 kg and 60 days of age, all of them reared in individual bins, were used. The animals were randomized to a completely randomized design with five treatments (diets) and nine replicates each. The level of acceptance of the meat decreased with the addition of increased levels of cottonseed. Increased levels of cottonseed resulted in an higher levels of saturated fatty acids (18:0) and polyunsaturated fatty acids (18:26-9,12) but reduced the levels of monounsaturated fatty acids (18:19-9) and odd- chain fatty acids (17:1n7-c10), which had a negative impact on the n6/n3 and nutritional relationships, in addition to the atherogenicity and thrombogenicity rates. The levels of tyrosine reduced with the addition of cottonseed. The levels of 1-penten-3-ol, 1-hexanol, benzyl alcohol, propanal, octanal, nonanal and furans decreased, while the levels of organosulphurs compounds increased in line with increasing levels of cottonseed. The pH values were not influenced by the levels of cotton seed. The lipids and ash content presented a significant difference, but were not adjusted by the linear or quadratic equations. The variables losses due to thawing and coesivity increased and water activity and water retention capacity reduced with the increment of cotton seed in the diet. On the other hand, the tocopherols, cooking losses, hardness and chewing were adjusted through quadratic equations. In the instrumental evaluation of color L*, b* and h° showed increasing linear behavior and the percentages of deoximioglobin decreased and of oxymioglobin increased. Soon, the increase in organosulfates and polyunsaturated fatty acids, especially linoleic acid, and the reduction of furans and some aldehyde compounds in line with increased levels of cottonseed in the diet, negatively influenced the sensorial acceptance of the meat. The inclusion of whole cottonseed in lambs fed up to 400 g Kg-¹ of dry matter, influences the physicochemical parameters evaluated in the meat, except protein content, moisture, cholesterol and shear force. The addition of the whole cottonseed in the diet increases the luminosity (L*) and the intensity of yellow (b*) of the meat, which makes it lighter and more yellowish.